One false note - Korman, Gordon (London : Scholastic, 2008)
A million dollars, or a clue? Police report a break-in at an elite hotel, and the suspects sound suspiciously like Amy and Dan. There's a car and speedboat chase and an angry mob! When there's a Clue on the line, anything can happen.
AR
106368
Keywords: Code and cipher stories; Children's stories; Wills -- Fiction; Mystery fiction; Scavenger hunts -- Fiction; Family secrets -- Fiction; Orphans -- Fiction; Clues -- Fiction; Adventure fiction; Brothers and sisters -- Fiction; Children's stories; Siblings -- Fiction; Family life -- Fiction; Mystery fiction; Adventure fiction; Vienna (Austria) -- Fiction; Austria -- Vienna; Code and cipher stories; Children's stories; Action and adventure fiction; Detective and mystery stories -- Juvenile fiction; Fiction; Juvenile works; Adventure fiction